Diagnosis of Cystic Teratoma Facilitated by Point-of-Care Ultrasonography. Issue 8 (August 2016) - Horner, Kimberly Bogard; Marin, Jennifer R.
Abstract : Abstract: Abdominal pain and constipation are common chief complaints in the pediatric emergency department. We present a case of a child with pain, abdominal distention, and constipation ultimately diagnosed with an ovarian teratoma and the role of point-of-care ultrasonography in the evaluation.